2011
DOI: 10.1186/1742-2094-8-28
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-α signals P115RhoGEF phosphorylation and RhoA activation in TNF-α-induced mouse brain microvascular endothelial cell barrier dysfunction

Abstract: BackgroundTumor necrosis factor-α (TNF-α), a proinflammatory cytokine, is capable of activating the small GTPase RhoA, which in turn contributes to endothelial barrier dysfunction. However, the underlying signaling mechanisms remained undefined. Therefore, we aimed to determine the role of protein kinase C (PKC) isozymes in the mechanism of RhoA activation and in signaling TNF-α-induced mouse brain microvascular endothelial cell (BMEC) barrier dysfunction.MethodsBend.3 cells, an immortalized mouse brain endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 33 publications
1
53
1
Order By: Relevance
“…Likewise, the isoform-selective PKC inhibitor Gö6976 [12-(2-cyanoethyl)-6,7,12,13-tetrahydro-13-methyl-5-oxo-5H-indolo(2,3-a)pyrrolo(3,4-c)-carbazole] prevented microvascular leakage during ischemia-reperfusion injury in the rat heart, as well as hyperpermeability in human coronary microvascular endothelium in response to IL-1␤ exposure (36). In addition, BBB dysfunction was mediated by PKC-␣ in response to tumor necrosis factor (TNF)-␣ exposure in mouse brain endothelium (29) and involved activation of PKC-and possibly other PKC isoforms during hypoxia in the rat brain (18,37). Based on these observations, we hypothesized that select PKC isoforms mediate hyperpermeability in human brain microvascular endothelium during IL-1␤ exposure.…”
mentioning
confidence: 85%
“…Likewise, the isoform-selective PKC inhibitor Gö6976 [12-(2-cyanoethyl)-6,7,12,13-tetrahydro-13-methyl-5-oxo-5H-indolo(2,3-a)pyrrolo(3,4-c)-carbazole] prevented microvascular leakage during ischemia-reperfusion injury in the rat heart, as well as hyperpermeability in human coronary microvascular endothelium in response to IL-1␤ exposure (36). In addition, BBB dysfunction was mediated by PKC-␣ in response to tumor necrosis factor (TNF)-␣ exposure in mouse brain endothelium (29) and involved activation of PKC-and possibly other PKC isoforms during hypoxia in the rat brain (18,37). Based on these observations, we hypothesized that select PKC isoforms mediate hyperpermeability in human brain microvascular endothelium during IL-1␤ exposure.…”
mentioning
confidence: 85%
“…These modifications further increase kinase activity of PKC (243). Several PKC inhibitors such as staurosporine, H7, calphostin C, bisindolylmaleimide, and chelerytherine inhibited endothelial hyper-permeability in response to different pro-inflammatory agents (133,200,341,358,460). A number of studies have demonstrated that membrane translocation and activation of the atypical isoforms of PKCf is required in thrombin-mediated increase in endothelial permeability (244,294).…”
Section: Pkcsmentioning
confidence: 99%
“…More recently, Arghef1 was also identified as the RhoA GEF mediated-RhoA activation and permeability induced by TNF-␣ (361) and LPS (546). Activation of Arhgef1 by TNF-␣ is mediated by PKC␣ phosphorylation of Arhgef1 (361).…”
Section: Rho Proteinsmentioning
confidence: 99%